Evidence of causal effect of major depression on alcohol dependence: findings from the psychiatric genomics consortium. Issue 7 (1st April 2019) - Polimanti, Renato; Peterson, Roseann E.; Ong, Jue-Sheng; MacGregor, Stuart; Edwards, Alexis C.; Clarke, Toni-Kim; Frank, Josef; Gerring, Zachary; Gillespie, Nathan A.; Lind, Penelope A.; Maes, Hermine H.; Martin, Nicholas G.; et al.
Abstract: Background: Despite established clinical associations among major depression (MD), alcohol dependence (AD), and alcohol consumption (AC), the nature of the causal relationship between them is not completely understood. We leveraged genome-wide data from the Psychiatric Genomics Consortium (PGC) and UK Biobank to test for the presence of shared genetic mechanisms and causal relationships among MD, AD, and AC. Methods: Linkage disequilibrium score regression and Mendelian randomization (MR) were performed using genome-wide data from the PGC (MD: 135 458 cases and 344 901 controls; AD: 10 206 cases and 28 480 controls) and UK Biobank (AC-frequency: 438 308 individuals; AC-quantity: 307 098 individuals). Results: Positive genetic correlation was observed between MD and AD (rgMD−AD = + 0.47, P = 6.6 × 10 −10 ). AC-quantity showed positive genetic correlation with both AD (rgAD−AC quantity = + 0.75, P = 1.8 × 10 −14 ) and MD (rgMD−AC quantity = + 0.14, P = 2.9 × 10 −7 ), while there was negative correlation of AC-frequency with MD (rgMD−AC frequency = −0.17, P = 1.5 × 10 −10 ) and a non-significant result with AD. MR analyses confirmed the presence of pleiotropy among these four traits. However, the MD-AD results reflect a mediated-pleiotropy mechanism (i.e. causal relationship) with an effect of MD on AD (beta = 0.28, P = 1.29 × 10 −6 ). There was no evidence for reverse causation. Conclusion: This study supports a causal role for genetic liability of MD on AD based on genetic datasets including thousands of individuals. Understanding mechanisms underlying MD-AD comorbidity addresses important public health concerns and has the potential to facilitate prevention and intervention efforts.